2016
DOI: 10.1212/nxg.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rare copy number variation in absence epilepsies

Abstract: Objective:To identify shared genes and pathways between common absence epilepsy (AE) subtypes (childhood absence epilepsy [CAE], juvenile absence epilepsy [JAE], and unclassified absence epilepsy [UAE]) that may indicate common mechanisms for absence seizure generation and potentially a diagnostic continuum.Methods:We used high-density single-nucleotide polymorphism arrays to analyze genome-wide rare copy number variation (CNV) in a cohort of 144 children with AEs (95 CAE, 26 UAE, and 23 JAE).Results:We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…More recently, a connection between sporadic GGEs and CNVs was observed in patients with 15q11.2, 15q13.3 and 16p13.11 microdeletions [8,9]. Moreover, the analysis of rare CNVs exclusively in absence epilepsy has found an association of this phenotype with two additional CNVs disrupting a range of important genes: 1q21.1 and Xp22.31 [10]. Interestingly, potentially causative CNVs are more often observed in patients with GGE plus intellectual disability than in patients with GGE only [11].…”
Section: Discussionmentioning
confidence: 97%
“…More recently, a connection between sporadic GGEs and CNVs was observed in patients with 15q11.2, 15q13.3 and 16p13.11 microdeletions [8,9]. Moreover, the analysis of rare CNVs exclusively in absence epilepsy has found an association of this phenotype with two additional CNVs disrupting a range of important genes: 1q21.1 and Xp22.31 [10]. Interestingly, potentially causative CNVs are more often observed in patients with GGE plus intellectual disability than in patients with GGE only [11].…”
Section: Discussionmentioning
confidence: 97%
“…Despite neurological abnormalities are frequent in CES, epilepsy is included in the minor features of the syndrome being reported only in about 6% of the cases (3). Recently, Addis et al (28), has shown that 22q11.2 duplication could be one of the gene pathway involved in the epileptogenesis of absence seizures. However, seizure characterization is lacking in CES.…”
Section: Discussionmentioning
confidence: 99%
“…Affordable technology that allows the identification of even small structural genomic alterations [i.e., copy number variations (CNVs)] was key to investigating the genetic basis for common neurodevelopmental disorders. Beginning with transformative studies of people living with autistic spectrum disorders (ASD) (Sebat et al, 2007;Pinto et al, 2010), we have come to understand that individually rare CNVs account for a significant proportion of the incidence not only of autism, but intellectual disability (Cooper et al, 2011), "idiopathic" generalized epilepsies (Mefford et al, 2010;Addis et al, 2016) and schizophrenia (Stefansson et al, 2008;Marshall et al, 2017), particularly where there is overlap between these conditions. Interestingly, genes identified from genome-wide association studies of particular disorders often overlap across disorder categories (Fromer et al, 2014; International League Against Epilepsy Consortium on Complex Epilepsies, 2014; Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014; Turner et al, 2017), suggesting that many of the genes have a broad neurodevelopmental role that may result in a range of recognizable syndromes or phenotypes.…”
Section: Severe De Novo Mutations and Genomic Alterations In Neurodevmentioning
confidence: 99%